Ankylosing Spondylitis, HLA-B27 and Klebsiella - An Overview: Proposal for Early Diagnosis and Treatment - Ebringer, Alan; Rashid, Taha; Wilson, Clyde; Ptaszynska, Teresa; Fielder, Mark (Current Rheumatology Reviews, 2006)
Ankylosing spondylitis (AS) is a potentially disabling rheumatic disease for which no curative treatment has yet been discovered. An extensive computer-based and manual search was undertaken to evaluate the role of microbes in the pathogenesis of AS. All together 147 papers were scrutinised. A total of 24 studies carried out on 1330 AS patients and 1191 healthy controls involving 15 different countries showed significantly elevated Klebsiella antibodies in AS patients when compared to controls. Molecular analysis has shown that Klebsiella microbes possess antigens, which cross-react with self-antigens, such as HLA-B27 and spinal collagens. Diagnostic criteria have been developed in which a person who is HLA-B27 positive and has clinical and laboratory evidence of an inflammatory backache for at least three months is proposed to have pre-AS. A specific elevation of anti- Klebsiella antibodies would confirm the diagnosis. A proposal for an early treatment using anti-Klebsiella measures is suggested. So far, apart from Klebsiella no other microbes have been shown to have a link with the development of AS. It is suggested that identifying and treating patients with Klebsiella reactive arthritis/pre-AS could involve the use of anti- Klebsiella measures, such as antibiotics and low starch diet together with immunosuppressive drugs in an endeavour to prevent the irreversible sequelae of established AS.
Keywords: Klebsiella